Taxonomy of the North Moroccan and Iberian species of the subgenus Amblypteraca (Coleoptera: Tenebrionidae: Pimeliinae: Pimelia) - Mas-Peinado, Paloma; Ruiz, José L.; Merkl, Ottó; Buckley, David; García-París, Mario (Zootaxa, 2021)
The subgenus Amblypteraca Mas-Peinado, Buckley, Ruiz & García-París, 2018 of Pimelia Fabricius, 1775, is restricted to the southern Iberian Peninsula and western Maghreb (northern and western Morocco). The distribution of Amblypteraca throughout the African-European edges overlaps largely with the geographic range of the subgenus Amblyptera, which is sister to the clade grouping subgenera Amblypteraca and Ecphoroma Solier, 1836. Delimiting species boundaries in the speciose genus Pimelia is often challenging, and the taxonomic status of some groups within the aforementioned subgenera is still a matter of debate. Here, we aim to stabilize some of the available names in Amblypteraca, and to correct some previous misidentifications. For that purpose, we discuss the composition and taxonomic structure within Amblypteraca by (i) assessing the phylogenetic congruence between mitochondrial and nuclear markers, and (ii) examining external morphological traits in 568 Amblypteraca specimens under the light of the phylogenetic hypotheses proposed here. Based on our results, Amblypteraca consists of three species: P. rotundipennis Kraatz, 1865, P. fairmairii Kraatz, 1865 and P. chrysomeloides Pallas, 1781. Both molecular and morphological data revealed four lineages within P. chrysomeloides: P. chrysomeloides chrysomeloides, distributed on both sides of the Strait of Gibraltar; P. chrysomeloides fornicata Herbst, 1799 from Portugal (Troia region); P. chrysomeloides bathyglypta Antoine, 1949, restricted to a narrow strip between Larache and Arbaoua (northern atlantic Moroccan coast), and P. chrysomeloides subris Koch, 1941 from Kenitra-La Mamora forest (Morocco). We designate a neotype of Tenebrio chrysomeloides Pallas, 1781 and propose the synonymy of P. chrysomeloides (Pallas, 1781) = P. obesa Solier, 1836 syn. n. Pimelia tristis Haag-Rutenberg, 1875, previously misidentified and included in Amblypteraca, is now transferred back to Amblyptera. Further studies with ad hoc sampling designs and analytical tools would be in need to delimit the exact geographic ranges of these taxa, and to analyse the patterns of diversity within and among species and subspecies.